Root temperature variation and photosynthesis of ’Valencia’ sweet orange nursery trees - Filho, José Rodrigues Magalhães; Machado, Eduardo Caruso; Machado, Daniela Favero São Pedro; Ramos, Rômulo Augusto; Ribeiro, Rafael Vasconcelos (Pesquisa Agropecuaria Brasileira, 2010)
The aim of this work was to evaluate the influence of the substrate temperature on gas exchange, photochemical activity and water relations in ’Valencia’ sweet orange grafted onto ’Rangpur’ lime. Six-month-old nursery trees were used. The experiment was carried out in a growth chamber, where the root system was maintained at 10, 20 (control) or 30ºC, the air temperature varied between 25 and 20ºC from day to night, the photoperiod and photosynthetic photon flux density were set to 12 hours and 800 mmol m-2 s-1, respectively. The CO2 assimilation rates in response to the intercellular CO2, chlorophyll a fluorescence and leaf water potential at 6 h and 13 h were measured for each treatment. The higher root temperature increased the CO2 assimilation in relation to the control temperature, due to diffusive and metabolic factors: plants showed enhanced maximum carboxylation efficiency (Vc, max), ribulose-1,5-bisphosphate regeneration (Jmax), and both stomatal (gs) and mesophyll (gi) conductances. The lowest root temperature led to increased alternative electron sink and decreased CO2 assimilation, due to diffusive and metabolic limitations, indicated by decreases in gs, gi, Vc, max, and Jmax.